Кримінальна відповідальність за кіберзлочини, вчинені під час збройного конфлікту: міжнародні тенденції та українські реалії - Юртаєва, К. В.; Yurtayeva, K. V.; Юртаєва Ксенія Володимирівна (Юридичний науковий електронний журнал. - 2022. - № 12. - С. 409-414, 2022)
Здійснено аналіз кримінальної відповідальності за кіберзлочини, вчинені під час збройного конфлікту, з врахуванням змін до КК України, внесених після 24 лютого 2022 року, та релевантних міжнародно-правових положень. Визначено, що внесення більшості змін до ст. 361 КК України не сприятиме підвищенню ефективності протидії кіберзлочинності в умовах дії воєнного стану та поліпшенню регулювання кримінальної відповідальності за акти кіберагресії, вчинені в умовах збройного конфлікту. Запропоновано здійснювати їх кваліфікацію статтями 113, 437 або 438 КК України в залежності від характеру та спрямованості вказаних протиправних посягань. Зазначені пропозиції здійснено з врахуванням передового світового досвіду в питанні кваліфікації кібероперацій, здійснюваних під час збройного конфлікту. Проаналізовано застосування норм міжнародного гуманітарного права до кібератак, спрямованих проти цивільних осіб і цивільних об’єктів. Наголошено, що безпрецедентні виклики в умовах розгортання гібридної війни проти України вимагають застосування проактивних підходів у забезпеченні кібербезпеки та врахування сучасного міжнародного досвіду в питаннях регулювання кримінальної відповідальності за кіберзлочини, вчинені під час збройних конфліктів.

The article analyses the issue of criminal liability for cybercrimes committed at the time of armed conflict considering amendments to the Criminal Code of Ukraine introduced after February, 24th 2022 and relevant international legal provisions. The relevance of the study is substantiated by the change of the character and severity of cyberthreats in the course of the Russian Federation aggression against Ukraine. The article provides detailed analyses of the amendments introduced to the Article 361-1 of the Criminal Code of Ukraine and a new version of the Article 361 of the Criminal Code of Ukraine. The conclusion is made about rashness of amendments introduced to the Article 361 of the Criminal Code of Ukraine: some of the newly introduced provisions render complexity to its application, some of its parts became completely inapplicable. Vast majority of the expressed criticisms concerns violation of the rules of legislative technique, the principle of legal certainty and consistency of the Ukrainian criminal law. The conclusion is made that majority of the amendments to the Article 361 of the Criminal Code of Ukraine will not increase efficiency in counteracting cybercrimes committed at the time of the armed conflict. To elaborate prospective law enforcement practice in counteracting cybercrimes committed at the time of the armed conflict the author suggests to qualify such actions under the Articles 113, 437 and 438 of the Criminal Code of Ukraine considering character and determination of the committed cybercrimes. The suggestions are supported by advanced international expertise in qualification of cyberoperations committed at the time of the armed conflict. The article analyses application of international humanitarian law to cyberattacks against civilians and civil objects. The article emphasizes unprecedented challenges posted to Ukraine by hybrid war that require proactive approaches to strengthening cybersecurity and considering relevant international experience in regulating criminal liability for cybercrimes committed at the time of the armed conflict. The conclusion is made about prospectiveness of further research of this issue within Ukrainian criminal law doctrine.

Проведен анализ уголовной ответственности за киберпреступления, совершенные во время вооруженного конфликта, с учетом изменений в УК Украины, внесенных после 24 февраля 2022 года, и релевантных международно-правовых положений. Установлено, что внесение большинства изменений в ст. 361 УК Украины не будет способствовать повышению эффективности противодействия киберпреступности в условиях военного положения и улучшению регулирования уголовной ответственности за акты киберагрессии, совершенные в условиях вооруженного конфликта. Предложено осуществлять их квалификацию статьями 113, 437 или 438 УК в зависимости от характера и направленности указанных противоправных посягательств. Указанные предложения осуществлены с учетом передового мирового опыта по квалификации киберопераций, осуществляемых во время вооруженного конфликта. Проанализировано применение норм международного гуманитарного права к кибератакам, направленным против гражданских лиц и гражданских объектов. Отмечено, что беспрецедентные вызовы в условиях развертывания гибридной войны против Украины требуют применения проактивных подходов в обеспечении кибербезопасности и учета современного международного опыта в вопросах регулирования уголовной ответственности за киберпреступления, совершенные в ходе вооруженных конфликтов.
Criminal liability for cybercrimes committed at the time of the armed conflict: international tendencies and Ukrainian realities
Keywords: Кримінальне право. Criminal Law. Уголовное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; кіберзлочини; cyber crimes; киберпреступления; кіберагресія; cyber aggression; киберагрессия; кримінальна відповідальність; criminal liability; уголовная ответственность; збройний конфлікт; armed conflict; вооруженный конфликт; законодавство; legislation; законодательство; міжнародне гуманітарне право; international humanitarian law; международное гуманитарное право